Adoption of improved forages in Western Kenya: Key underlying factors - Oulu, Martin; Notenbaert, An Maria Omer (2020)
To understand the underlying reasons why farmers wish to take up or try improved forages in four counties in Western Kenya and why they subsequently adopt or not adopt the technology. Secondary objectives: Take a gendered perspective by distinguishing between the motivations for adoption as well as challenges facing male and female adopters, and Review the assumptions of the project in terms of why farmers want to intensify farm systems. Justification: Study results to be used by the Grass2Cash project to promote and upscale grass varieties that are well adapted to local conditions and future climate conditions while simultaneously producing high yields of good nutritional value.